Internationalization of Russian Education: New Challenges and New Solutions - V. K. Nikolayev; A. A. Skvortsov; R. S. Nikolaev; S. A. Bogatenkov (Высшее образование в России)
Today, the export of education in Russia continues to be an important state strategy of the Russian government, despite sanctions measures by European states and a decrease in the intensity of international cooperation with European countries. In 2022, the President of the Russian Federation set new goals for the export of education, according to which by 2030 the number of foreign students on higher education programs in Russian universities and scientific organizations should reach a minimum of 500 thousand people. Russia’s current foreign policy for the development and expansion of militarypolitical and trade-economic ties and common geopolitical realities have put on the agenda the development of new tools for international scientific and educational cooperation. The study aims to propose an effective strategy for the current state of the Russian education export from the perspective of a new geography and forms of international cooperation for increased activity on the global education market. The methodological basis of the study was formed by methods of comparative analysis of the domestic and foreign experience of higher education export, as well as systematization, generalization and interpretation of statistical information, posted on the websites of the Ministry of Science and Higher Education of the Russian Federation, leading Russian and foreign universities, authorities, and analytical agencies. The main result of the study is an analysis of the tools and mechanisms for expansion of the geography of the Russian education export and the promotion of the competitive brand of the Russian universities in conditions of isolation. The article shows that these tools allow to solve multifaceted tasks including the creation of a positive basis for political and economic interaction and training specialists in Russia and abroad to implement joint plans for the development of various areas of cooperation. The article contains the proposals for expanding the export of Russian education in view of new geopolitical realities. The CIS, Asia, Africa and Latin America are considered as the key partners.